2016
DOI: 10.3389/fpls.2016.01659
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Aquaporins: The Solute Factor

Abstract: In the recent years, the biophysical properties and presumed physiological role of aquaporins (AQPs) have been expanded to specialized cells where water and solute exchange are crucial traits. Complex but unique processes such as stomatal movement or pollen hydration and germination have been addressed not only by identifying the specific AQP involved but also by studying how these proteins integrate and coordinate cellular activities and functions. In this review, we referred specifically to pollen-specific A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…No interaction between SYP131 and PIP2;7 was reported in SUS assays by Jones et al (2014) and no PIP2;7 expression was reported in the pollen in proPIP2;7:GUS lines ( Da Ines, 2008 ; Prado et al, 2013 ; Hachez et al, 2014 ). However, large-scale data revealed that PIP2;7/2;8 (the probe used cannot differentiate between both isoforms), are expressed during pollen development but not in mature pollen ( Pérez Di Giorgio et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…No interaction between SYP131 and PIP2;7 was reported in SUS assays by Jones et al (2014) and no PIP2;7 expression was reported in the pollen in proPIP2;7:GUS lines ( Da Ines, 2008 ; Prado et al, 2013 ; Hachez et al, 2014 ). However, large-scale data revealed that PIP2;7/2;8 (the probe used cannot differentiate between both isoforms), are expressed during pollen development but not in mature pollen ( Pérez Di Giorgio et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco, PIP genes are suggested to be involved in the movement of water between pollen and stigma ( Bots et al, 2005 ). However, the role of TIP1-1 and TIP2-1 in pistil remains elusive ( Pérez Di Giorgio et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides studies in plants and animals that have been separately presented, there are features that can be compared, such as those described in the reproductive systems. In plants, specific pollen AQPs have been reported, such as TIP1;3, TIP5;1, NIP4;1 and NIP4;2 (Soto et al 2008;Pérez Di Giorgio et al 2016a, 2016b. These reproduction-associated AQPs showed low water permeability but the capacity to transport glycerol and urea, and have been suggested to be involved in the nitrogen metabolic pathway during pollen tube growth (Soto et al 2008(Soto et al , 2010Pérez Di Giorgio et al 2016a, b).…”
Section: The Pathological Focus In Animalsmentioning
confidence: 99%
“…Since the first water channel report (Preston et al 1992), the discovery of AQPs had a significant impact on the study of water and solute transport. However, the view of AQPs as specific water channels has been changing due to large amount of evidence showing that some AQPs carry small solutes or gases, and others are expressed in tissues where water flow dynamics appear to be less relevant (Bienert et al 2008;Kitchen et al 2015b;Pérez Di Giorgio et al 2016a, 2016b.…”
Section: What Are Aqps Formentioning
confidence: 99%
See 1 more Smart Citation